Describing the evolution of mobile technology usage for Latino patients and comparing findings to national mHealth estimates - Arora, Sanjay (J Am Med Inform Assoc, 2016)
Objectives Describe the change in mobile technology used by an urban Latino population between 2011 and 2014, and compare findings with national estimates. Materials and Methods Patients were surveyed on medical history and mobile technology use. We analyzed specific areas of mobile health capacity stratified by chronic disease, age, language preference, and educational attainment. Results Of 2144 Latino patients, the percentage that owned a cell phone and texted were in-line with Pew estimates, but app usage was not. Patients with chronic disease had reduced access to mobile devices (P < .001) and lower use of mobile phone functionalities. Discussion Prior research suggests that Latinos can access mHealth; however, we observed lower rates among Latino patients actively seeking heath care. Conclusion Published national estimates do not accurately reflect the mobile technology use of Latino patients served by our public safety-net facility. The difference is greater for older, less educated patients with chronic disease.